Relationship of University-Industry Cooperation and Innovative Activities: Case Study of Croatia, Czech Republic and Hungary - Prokop, Viktor; Odei, Samuel Amponsah; Stejskal, Jan (Marketing & Menedzsment, 2018)
THE AIMS OF THE PAPER Cooperation has no boundaries; we called it trans-sector cooperation (mostly university-industry and the government can be also incorporated). The knowledge and industrial sector cooperation is the most common now. The knowledge sector is perceived as a contractor (or creator) of various knowledge. Industrial enterprises use this knowledge for the emergence of innovation and also for commercialization. The advantages of cooperation are mutual, because it gives the possibility of implementing further basic and applied thereafter (industrially exploitable) research for the universities. Research institutions acquire also additional resources and cooperation allows their students to engage in practical issues. Enterprises acquire from the cooperation relatively cheap source of new knowledge, access to instrument and technological equipment. In regions, there are different tools on the principle of knowledge sharing and cooperation. These include for instance industrial clusters or business networking, as well as regional innovation systems and global production chains. The applications of public incentives and subsidies from public budgets are often applied because they are perceived as of regional policy tools. But there is the question about the efficiency of this public support, as well as about the efficiency of the cooperation among the mentioned entities. METHODOLOGY Therefore, we analyse the influence of University-Industry cooperation and public financing (from national and European funds) on the growth of turnover from innovated products in manufacturing industries in Croatia, Czech Republic and Hungary by using own multiple linear regression models and data from the Eurostat (CIS database) between the years 2010-2012. MOST IMPORTANT RESULTS In total, we analysed 7 189 firms, and the results show, that this kind of cooperation influence firms’ innovation activities differently within each country. RECOMMENDATIONS We therefore recommend industries to strengthen their cooperation with universities and public research institutes, clients, customers and other competitors through improving trust and better management.